1997
DOI: 10.1007/s001050050642
|View full text |Cite
|
Sign up to set email alerts
|

Hypomelanosis guttata idiopathica

Abstract: A 37-year-old white female with dark complexion presented with progressive hypopigmented macules on the face and upper trunk. She was in good health and her family history was unremarkable. Histologic examination of the hypopigmented patches revealed reduced melanin within the basal layers of the epidermis. Using immunohistochemical and ultrastructural studies, the number of melanocytes appeared normal but signs of degeneration were evident and dendrites were shortened. The diagnosis of idiopathic guttate hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
15

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 14 publications
(27 reference statements)
0
7
0
15
Order By: Relevance
“…All the components of the basal membrane complex were normal. Schiller, Metze and Böhm, found that melanocytes in IGH had fewer or no dendrites . Τhe number of the melanocytes was normal but they showed degenerative changes, i.e.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…All the components of the basal membrane complex were normal. Schiller, Metze and Böhm, found that melanocytes in IGH had fewer or no dendrites . Τhe number of the melanocytes was normal but they showed degenerative changes, i.e.…”
Section: Discussionmentioning
confidence: 91%
“…Schiller, Metze and B€ ohm, found that melanocytes in IGH had fewer or no dendrites. 5 Τhe number of the melanocytes was normal but they showed degenerative changes, i.e. the cytoplasm was swollen and the endoplasmic reticulum was hyperplastic.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Genetic factors may also play a role in this condition. 15,16 Medical therapy for idiopathic guttate hypomelanosis includes corticosteroids, either topical or intralesional, and retinoids, typically topical tretinoin. One report describes successful treatment with pimecrolimus 1% ; however, caution is warranted because the author has anecdotal experience possibly suggesting that topical calcineurin inhibitors may be linked to the development of idiopathic guttate hypomelanosis in immunosuppressed patients.…”
Section: Discussionmentioning
confidence: 99%